6x+60=-45

Simple and best practice solution for 6x+60=-45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+60=-45 equation:



6x+60=-45
We move all terms to the left:
6x+60-(-45)=0
We add all the numbers together, and all the variables
6x+105=0
We move all terms containing x to the left, all other terms to the right
6x=-105
x=-105/6
x=-17+1/2

See similar equations:

| x^2+0.1x+10^4=0 | | 2y-3(2y-3)+3=31 | | 9x^2+34x−11=−3 | | 3(3x+4)5=9x+(-2) | | x*0.6=x-24.375 | | x*0.6=x-40 | | 1/3^x=243 | | 5+2x=-x+2 | | 4(2x+1)=5x+3x+ | | 1+3p=p+3 | | 1+3p=p=3 | | 1=3p=p= | | 4x+6/3=×+9/2 | | 1=3p=p=3 | | 2.4=4.6+0.2v | | 7(c-12=93 | | 5(c+4)=120 | | -29=(29-1)+2a | | -4(x-6)=48 | | 4^(2x-3)=2^3 | | 6x+(-66)=36 | | 3(4x^2)^2-12x=0 | | 3(a+3)=39 | | 4^(5-3x)=1/256 | | -y/4=0 | | -y/2=0 | | -2(m+8)=-48 | | 14x-14x=15+2x-3 | | 5x-21=2(x-6) | | 10h-100=-10 | | X^2+4x+2x=224 | | 10−2h=8 |

Equations solver categories